2017
DOI: 10.3390/molecules22091451
|View full text |Cite
|
Sign up to set email alerts
|

Coordination Mechanism and Bio-Evidence: Reactive γ-Ketoenal Intermediated Hepatotoxicity of Psoralen and Isopsoralen Based on Computer Approach and Bioassay

Abstract: Psoralen and isopsoralen are secondary plant metabolites found in many fruits, vegetables, and medicinal herbs. Psoralen-containing plants (Psoralea corylifolia L.) have been reported to cause hepatotoxicity. Herein, we found that psoralen and isopsoralen were oxidized by CYP450s to reactive furanoepoxide or γ-ketoenal intermediates, causing a mechanism-based inhibition of CYP3A4. Furthermore, in GSH-depleted mice, the hepatotoxicity of these reactive metabolites has been demonstrated by pre-treatment with a w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 55 publications
(59 reference statements)
0
9
0
Order By: Relevance
“…Psoralen is a well-known active compound present in psoraleae fructus (Bu Gu Zhi), a traditional Chinese medicine comprising the dried ripe fruit of Psoralea corylifolia L. (Lu et al, 2014; Zheng et al, 2017). Previous studies have demonstrated that psoralen induces hepatotoxicity in mice (Hai et al, 2017). In the present study, we assessed the developmental toxicity of psoralen in zebrafish embryos/larvae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Psoralen is a well-known active compound present in psoraleae fructus (Bu Gu Zhi), a traditional Chinese medicine comprising the dried ripe fruit of Psoralea corylifolia L. (Lu et al, 2014; Zheng et al, 2017). Previous studies have demonstrated that psoralen induces hepatotoxicity in mice (Hai et al, 2017). In the present study, we assessed the developmental toxicity of psoralen in zebrafish embryos/larvae.…”
Section: Discussionmentioning
confidence: 99%
“…Psoralen polymer-lipid hybrid nanoparticles cause reversal of multidrug resistance in MCF-7/ADR cells (Huang Q. et al, 2018). The toxicity of psoralen has recently come under the microscope, and hepatotoxicity of psoralen has recently been observed in vitro and in vivo (Diawara et al, 2000; Hai et al, 2017; Li Z.J. et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Furocoumarins, including psoralen and isopsoralen, are widely used in the clinic. Previous studies by our group have indicated that their metabolites do produce certain serious drug interactions and toxicity through biotransformation and other processes (34,35). Relevant documents include studies by Yang et al (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies found that psoralen exhibited mechanism-based inactivation (also called irreversible inactivation) of CYP2A6 (Koenigs and Trager, 1998a). and CYP2B1 (Koenigs and Trager, 1998b), in addition to CYP2B6 (Ji et al, 2015) and CYP3A4 (Liu and Flynn, 2015;Hai et al, 2017), which were oxidized by psoralen to produce the reactive metabolite furanoepoxide, suggesting that the metabolite exerted an inhibitory effect rather than the parent compound. In addition, Hai et al found that the active metabolites can be inactivated by H 2 O and GSH in the liver, helpful for the safe intake of fruits and vegetables containing psoralen, to a certain extent (Hai et al, 2017).…”
Section: Liver Damagementioning
confidence: 99%
“…Psoralen is a principal bioactive component of Cullen corylifolium(L.)Medik, and is also found in many vegetables and fruits, such as Apium graveolens L and Ficus carica L. As shown in Figure 1, psoralen is a tricyclic coumarin-like aromatic compound, the molecular structure of which is 7H-Furo[3, 2-g] benzopyran-7-one (molecular weight: 186.16; molecular formula: C 3 H 6 O 3 ) (Sui et al, 2020). Psoralen is widely used as a quality control component in herbal formulae such as Sishen Wan, Yaotong Pian, and Wenweishu Jiaonang (Ji et al, 2015;Hai et al, 2017), and combined with ultraviolet-A light for the treatment of psoriasis, vitiligo, and eczema (Madigan and Lim, 2016). This article will review the pharmacological properties of psoralen, including its anti-osteoporosis, anti-tumor, anti-viral, antibacterial and anti-inflammatory effects, and its toxicity.…”
Section: Introductionmentioning
confidence: 99%